Is the Borneo Palm Oil Plantation Company Categorized in Investment Grade? - Saratian, Eko Tama Putra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to identify which oil palm plantations in the Kalimantan region are currently entering the replanting stage and which are rated as